MgB2 for MRI applications: dual sintering induced performance variations in in situ and IMD processed MgB2 conductors. Issue 7 (22nd January 2020) - Patel, Dipak; Matsumoto, Akiyoshi; Kumakura, Hiroaki; Maeda, Minoru; Kim, Su-Hun; Al Hossain, Md Shahriar; Choi, Seyong; Kim, Jung Ho
Abstract : Dual sintering induced performance variations in MgB2 superconductors are studied in detail in relation to MRI applications. Abstract : Magnesium diboride (MgB2 ) is known to have good potential to be used in a commercial liquid helium-free magnetic resonance imaging (MRI) magnet. The magnet is expected to be fabricated using reacted MgB2 conductors to minimize modifications in the existing magnet production technologies and operated in the persistent mode by forming a closed-loop using superconducting joints. The superconducting joints of the reacted MgB2 conductors are typically formed by placing unreacted magnesium and boron powders in between them followed by sintering. During this process, the MgB2 conductors will inevitably experience dual sintering in the vicinity of the superconducting joints. However, the effects of dual sintering on the performance of MgB2 conductors are still unknown. Therefore, herein, we dual sintered commercially available multifilament in situ and laboratory-made monofilament internal magnesium diffusion (IMD) processed MgB2 conductors (un-doped and C-doped) and evaluated their transport performance, microstructure, lattice parameters, and critical temperature in detail. In the IMD processed wires, the C-doped boron powder was found to promote a better diffusion of magnesium compared with the un-doped boron powder. Under typical dual sintering conditions, surprisingly, the C-doped in situ wire showed a simultaneous improvement in the engineering critical current density and n -value in different magnetic fields at 4.2 K and 20 K. On the other hand, the remaining conductors showed a strong dual sintering induced transport performance variation. Our findings provide insights into MgB2 conductors' performance after dual sintering for their further development towards MRI applications.